PRESCHOOL EDUCATION SYSTEM IN FOREIGN COUNTRIES - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
The article talks about preschool education and information is given about the preschool education system in developed countries. Opinions were mentioned that it is necessary to study the system of preschool education in foreign countries and apply their best practices in accordance with our conditions.